Kebutuhan Alat Teknis Reklamasi PIT 3 Selatan PT. Wijaya Mandiri Energi di Kabupaten Paser, Kalimantan Timur - Galih Handhika; Henny Magdalena; Lucia Litha Respati (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Reclamation is an activity carried out throughout the stages of the mining business to organize, restore, and improve the quality of the environment and ecosystem so that it can function again according to its designation (Law No. 3 of 2020). In PT Wijaya Mandiri Energi's mining activities that have been completed, the required activity is to carry out reclamation. In planning reclamation activities, technical reclamation tools are needed. Therefore, in this study, calculations were carried out to determine the number of technical equipment requirements used in reclamation activities that will be carried out in pit 3 south. Based on observations of mining activities carried out in pit 3 south, data is obtained in the form of productivity values of digging-loading equipment, transport equipment and displacement equipment. In this research, the quantitative analysis method is used by calculating the value of the area, productivity and actual working hours so as to obtain the value of the need for digging tools, transport tools and displacement tools needed in reclamation activities to achieve optimal value. As for the research conducted with an area of 5.95Ha and a production target of 208,250 m3, with the productivity of Doosan 500LCV excavator equipment of 218.64 m3 / hour, dump truck of 58.84 m3 / hour and SEM 822D bulldozer of 351.64 m3 / hour, the number of excavator Doosan 500LCV digging and loading equipment is 2 units, Beiben 2642 dump truck of 8 units and SEM 822D bulldozer of 2 units.